Global Impact of Menstrual Readiness Revolution: Dampak Global Revolusi Kesiapan Menstruasi - Novia Putri Widyawati; Yanik Purwanti; Nurul Azizah (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the association between menstrual knowledge and readiness for menarche among sixth-grade girls at SDN Ngembe 1 Beji in 2023. Using a cross-sectional approach and validated questionnaires, the research explores factors beyond knowledge that influence preparedness. Findings reveal a non-significant correlation (p-value = 0.636) between knowledge and readiness, emphasizing the need for comprehensive educational efforts involving healthcare, schools, and communities to better equip young women for this important phase of development. Highlight: Holistic education for menstrual readiness. Cross-sectional study on adolescent knowledge. Health promotion strategies for menstrual preparedness. Keyword: Menstrual knowledge, Menarche readiness, Adolescent education, Cross-sectional study, Health promotion